The Perzyna Viscoplastic Model in Dynamic Behaviour of Magnetorheological Fluid under High Strain Rates - FRĄŚ, Leszek (Engineering Transactions, 2015)
The extension of viscoplastic model of Perzyna for the field of magnetorheological materials is proposed. Perzyna’s approach is adopted to identify the mechanisms of microscopic rearrangement of ferroelements producing visible increase of material stiffness, in particular increase of shear modulus. The project of laboratory test stand is presented. It is based on Split-Hopkinson pressure bar set-up equipped with container for magnetorheological fluid and coil to control it.